Baseline Heart Rate, Sensation Seeking, and Aggression in Young Adult Women: A Two‐Sample Examination. Issue 4 (8th March 2013) - Wilson, Laura C.; Scarpa, Angela
Abstract Although substantial literature discusses sensation seeking as playing a role in the relationship between baseline heart rate and aggression, few published studies have tested the relationships among these variables. Furthermore, most prior studies have focused on risk factors of aggression in men and have largely ignored this issue in women. Two samples (n = 104; n = 99) of young adult women completed measures of resting heart rate, sensation seeking, and aggression. Across the two samples of females there was no evidence for the relationships of baseline heart rate with sensation seeking or with aggression that has been consistently shown in males. Boredom susceptibility and disinhibition subscales of sensation seeking were consistently significantly correlated with aggression. The lack of significance and the small effect sizes indicate that other mechanisms are also at work in affecting aggression in young adult women. Finally, it is important to consider the type of sensation seeking in relation to aggression, as only boredom susceptibility and disinhibition were consistently replicated across samples. Aggr. Behav. 39:280–289, 2013. © 2013 Wiley Periodicals, Inc.